REGULATION FOR E-COMMERCE PLATFORM PROVIDERS IN INDONESIA: IMPORTANCE AND EFFECTIVENESS - Confido, Jemy Vestius (Lex Prospicit, 2023)
Indonesia is a country with the largest digital economy potential in Southeast Asia as indicated by number of its internet user especially through mobile access. This huge potential begins to realize with the presence of electronic commerce (e-Commerce) services which grow very fast and very vastly. The presence of e-Commerce has stimulated many new social phenomena, which are mainly triggered by e-Commerce platform providers who intensively perform marketing activities. This situation will become the real law (das sein) if it is not governed by law.The purpose of this research is to analyze the importance and effectiveness of existing regulations regarding e-Commerce platform providers in Indonesia. The research applies normative juridical method that uses applicable laws and regulations relevant to the issues as the primary sources supported by empirical cases as the secondary sources. From theoretical perspective, responsive law theory and the principle of lex specialis derogat legi generali are applied in this research. The applied positive laws must be assured for their responsiveness toward social needs while the specific characteristics of e-Commerce are entirely considered. Legal comparisons with international laws and other countries are also included to enrich the analysis.The research concludes that the Government Regulation Number 80 of year 2019 regarding Trading through Electronic System is very important to regulate e-Commerce environment in Indonesia. However, the enforcement of this regulation is not fully effective. The government of Indonesia could apply the regulation to facilitate healthy e-Commerce growth with comprehension towards business perspective and building trust to stimulate expected responses. Effective implementation of comprehensive e-Commerce regulation will strengthen the nation’s digital economy and overall economic resilience. Specific legal arrangements for e-Commerce platform providers should not paralyze the business. Instead, more persuasive approaches with good communication and trust will stimulate positive benefits to all related parties.Bahasa Indonesia Abstrak: Indonesia merupakan negara dengan potensi ekonomi digital terbesar di Asia Tenggara sebagaimana diindikasikan oleh jumlah pengguna internet khususnya yang menggunakan akses seluler. Potensi yang besar ini mulai terwujud menjadi nyata dengan kehadiran layanan perdagangan elektronik atau e-Commerce yang tumbuh secara cepat dan besar. Kehadiran e-Commerce telah memicu fenomena-fenomena sosial yang utamanya didorong oleh penyedia layanan platform e-Commerce yang secara intensif melakukan aktivitas pemasaran. Situasi ini akan menjadi hukum yang digunakan (das sein) jika tidak ditata oleh regulasi hukum.Tujuan dari penelitian ini adalah untuk menganalisa pentingnya dan keefektifan dari regulasi yang sudah ada mengenai penyedia platform e-Commerce di Indonesia.  Penelitian ini menggunakan metode yuridis normatif yang bertumpu kepada hukum dan regulasi yang diberlakukan sesuai dengan isu tersebut sebagai sumber utama dengan didukung kasus-kasus empiris sebagai sumber pelengkap. Dari sudut pandang teoritis, teori hukum responsif dan asas lex specialis derogat legi generali digunakan sebagai alat analisis dalam penelitian ini. Hukum positif yang diberlakukan harus dipastikan  bersifat responsif terhadap kebutuhan masyarakat sedangkan karakteristik khusus dari e-Commerce harus seluruhnya dipertimbangkan. Perbandingan dengan hukum international dan negara-negara lain juga digunakan untuk memperkaya analisis.Penelitian ini menyimpulkan bahwa Peraturan Pemerintah Nomor 80 Tahun 2019 tentang Perdagangan Melalui Sistem Elektronik sangatlah penting untuk mengatur lingkungan e-Commerce di Indonesia. Namun demikian, penegakan dari peraturan ini tidak sepenuhnya efektif. Pemerintah Indonesia bisa menerapkan peraturan ini untuk memfasilitasi pertumbuhan e-Commerce yang sehat dengan pemahaman terhadap perspektif bisnis dan pembentukan kepercayaan untuk merangsang response yang diharapkan. Implementasi yang efektif dari peraturan e-Commerce yang komprehensif akan memperkuat ekonomi digital dan keseluruhan daya tahan ekonomi nasional. Pengaturan khusus terhadap penyedia platform e-Commerce seyogyanya tidak melumpuhkan bisnis. Sebaliknya, pendekatan yang lebih persuasif dengan komunikasi yang baik dan kepercayaan akan mendorong manfaat positif baik semua pihak terkait.